2007
DOI: 10.1111/j.1742-1241.2007.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe-associated adverse effects: what the clinician needs to know

Abstract: Ezetimibe is a safe alternative option for hyperlipidaemic patients intolerant to other lipid lowering drugs as well as a beneficial supplementary agent for patients who do not reach the recommended serum cholesterol level with their current hypolipidaemic treatment. However, as is the case with all new medications, physicians should be alert to recognise adverse effects associated with ezetimibe and report them to regulatory authorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 85 publications
1
43
0
3
Order By: Relevance
“…Combination treatment was well-tolerated (three withdrawals) 30 . These findings are in accordance with most studies showing that ezetimibe, alone or in combination with statins, was not associated with increased rates of myopathy or rhabdomyolysis 31 . A meta-analysis of randomized controlled trials, which involved 5039 patients, assessed the efficacy and safety of adding ezetimibe 10 mg/day to ongoing statin treatment 32 .…”
Section: Efficacysupporting
confidence: 82%
“…Combination treatment was well-tolerated (three withdrawals) 30 . These findings are in accordance with most studies showing that ezetimibe, alone or in combination with statins, was not associated with increased rates of myopathy or rhabdomyolysis 31 . A meta-analysis of randomized controlled trials, which involved 5039 patients, assessed the efficacy and safety of adding ezetimibe 10 mg/day to ongoing statin treatment 32 .…”
Section: Efficacysupporting
confidence: 82%
“…(42) The FDC of atorvastatin plus ezetimibe in our study was well-tolerated, with a safety profile comparable to that of atorvastatin monotherapy. Mild dyspepsia was the only adverse event encountered in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Deficiency of acid SMase in hepatic cells may increase the risk of inflammation and proliferation, due to the resistance to apoptosis. Although ezetimibe is considered as a safe drug, case reports recently showed that it may induce liver swelling, hepatitis, and abnormal changes in liver enzymes [34][35][36][37]. How the reduction of acid SMase by ezetimibe may be involved in these phenomena is unknown.…”
Section: Discussionmentioning
confidence: 99%